Pengaruh Model Pembelajaran SAVI (Somatic, Auditory, Visualization, Intellectualy) Terhadap Hasil Belajar IPA Siswa Kelas IV SD Negeri 2 Trimulyo Kecamatan Tanjung Bintang Kabupaten Lampung Selatan - Anggraissi, Hani Safitri; Qomario, Qomario; Mashari , Ali (JURNAL ILMU PENDIDIKAN, 2023)
The relationship between the SAVI learning model (somatic, auditory, visualization, intellectualy) and scainse learning outcomes for fourth grade student at SD Negeri 2 Trimulyo, Tanjung Bintang District, South Lampung Selatan. This study aims to describe whether there is an influence of the SAVI learning model (somatic, auditory, visualization, intellectualy) and scainse learning outcomes for fourth grade student at SD Negeri 2 Trimulyo, Tanjung Bintang District, South Lampung Selatan. The survey results show that student learning outcomes are still low. This type of research is quantitave with pre-experimental in the form of one group pretest-posttest design. The population in this study were fourth grade students at SD Negeri 2 Trimulyo. The sampel for this study consisted of 24 students. Data collection techinques using tests, documentation, data analysis techniques, and by using the t-test. The results of the study are shown by the results of the t-test (paired sample t test) for the same sample with different treatment (pretest-posttest) with a tcount of 12,477 with a Sig (2-tailed) level of 0,000 < 0.05 which proves that there is an influence of the learning model SAVI  (somatic, auditory, visualization, intellectualy) on learning outcomes.